Pengaruh Penggunaan Shopee Paylater Dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi - Resna Martawarni Samaloisa; Dessyta Gumanti; Serli Diovani Teza (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze the effects of Shopee PayLater usage and financial literacy on the consumptive behavior of Economics Education students at the Faculty of Teacher Training and Education (FKIP), Ekasakti University, both partially and simultaneously. The research employed a quantitative approach with a population that also served as the sample, consisting of 54 students selected through total sampling. Data were analyzed using multiple linear regression, while hypothesis testing was conducted using t-tests and an F-test. The results show that Shopee PayLater usage has a significant effect on consumptive behavior (t_calculated = 2.146 > t_table = 1.672; sig = 0.037 < 0.05). Financial literacy also has a significant effect on consumptive behavior (t_calculated = 2.878 > t_table = 1.672; sig = 0.006 < 0.05). Simultaneously, Shopee PayLater usage and financial literacy have a positive and significant effect on students’ consumptive behavior (F_calculated = 17.489 > F_table = 2.400; sig = 0.000 < 0.05). These findings confirm that students’ consumptive behavior is influenced by the use of PayLater services and their level of financial literacy.